2017
DOI: 10.1038/srep42829
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Comparative transcriptomic analysis uncovers the complex genetic network for resistance to Sclerotinia sclerotiorum in Brassica napus

Abstract: Scientific Reports 6: Article number: 19007; published online: 08 January 2016; updated: 21 February 2017. The original version of this Article contained an incorrect version of Supplementary Table S7. This error has now been corrected in the HTML version of this Article; the PDF version was correctat the time of publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…68 Some genes involved in pathogen recognition, such as the MAPK cascade, the JA/ET synthesis and signaling pathway, and the lignin synthesis pathway were also differentially expressed between SSR-resistant and -susceptible accessions. 50,88 In addition, the abundance of transcripts of genes related to glucosinolate and phenylpropanoid biosynthesis, and the content of glucosinolates were also significantly increased in the resistant accessions, which indicated that secondary metabolite production might be a key component in B. napus resistance against S. sclerotiorum. 68,88 The interaction between B. napus and S. sclerotiorum was also strictly regulated at the microRNA (miRNA) level.…”
Section: Functional Genomics Analysis Of the Molecular Mechanisms Of ...mentioning
confidence: 97%
See 3 more Smart Citations
“…68 Some genes involved in pathogen recognition, such as the MAPK cascade, the JA/ET synthesis and signaling pathway, and the lignin synthesis pathway were also differentially expressed between SSR-resistant and -susceptible accessions. 50,88 In addition, the abundance of transcripts of genes related to glucosinolate and phenylpropanoid biosynthesis, and the content of glucosinolates were also significantly increased in the resistant accessions, which indicated that secondary metabolite production might be a key component in B. napus resistance against S. sclerotiorum. 68,88 The interaction between B. napus and S. sclerotiorum was also strictly regulated at the microRNA (miRNA) level.…”
Section: Functional Genomics Analysis Of the Molecular Mechanisms Of ...mentioning
confidence: 97%
“…50,88 In addition, the abundance of transcripts of genes related to glucosinolate and phenylpropanoid biosynthesis, and the content of glucosinolates were also significantly increased in the resistant accessions, which indicated that secondary metabolite production might be a key component in B. napus resistance against S. sclerotiorum. 68,88 The interaction between B. napus and S. sclerotiorum was also strictly regulated at the microRNA (miRNA) level. 91,92 Cao et al 93 identified 68 differentially expressed miRNAs between the SSR-inoculated and uninoculated leaves, some of which targeted plant defense or resistance-related genes, with three miRNAs targeting key components of post-transcriptional gene silencing (PTGS), AGO1 and AGO2.…”
Section: Functional Genomics Analysis Of the Molecular Mechanisms Of ...mentioning
confidence: 97%
See 2 more Smart Citations